The relationship between hypertriglyceridemic wait-to-height ratio and hypertension–diabetes comorbidity among older adult - Zhang, Ping; Xiong, Yangyang; Chen, Menghan; Zhang, Huaide; Sun, Nan; Wu, Fan; Yang, Jiayu; Ren, Yongcheng (Frontiers in Public Health, 2023)
Objective: Limited information is available on the effect of hypertriglyceridemic waist-to-height ratio (HTHWH) and hypertension-diabetes comorbidity (HAD) in elderly people. We aimed to explore the relationship between HTHWH and HAD for the co-management of hypertension and diabetes mellitus in the elderly.Methods: Cross-sectional study, randomized cluster sampling from 10 community health service centers, and multivariate logistic regression were used in this study.Recruit between January 2019 and December 2020, and 3501 participants aged 65 years or older completed the study.Results: Among 3501 participants, the median age was 69.96 years and 42.50% were men. 1207 subjects were in the HTHWH group and the prevalence rate of HAD was 17.23% in this group. Multivariate logistic regression analysis showed that as compared with the normal group, the risk of HAD in the HTHWH group increased by 2.05 times (OR=3.05, 95%CI: 2.06-4.51). The risks of hypertension or diabetes mellitus (HOD), hypertension, diabetes mellitus were also increased in the HTHWH group, with their ORs(95%CIs) being 1.82 (1.44-2.29), 1.73 (1.38-2.17), and 2.28(1.66-3.13), respectively.HTHWH significantly increases the risk of HAD and can be used as a reliable tool to screen the high-risk population of HAD.